Microbial concrete: Way to enhance the durability of building structures - Achal, V.; Mukherjee, Abhijit; Reddy, M. (American Society of Civil Engineers (ASCE), 2011)
Natural processes, such as weathering, faults, land subsidence, earthquakes, and human activities, create fractures and fissures in concrete structures that can reduce the service life of the structures. A novel strategy to restore or remediate such structures is biomineralization of calcium carbonate using microbes, such as those in the genus of the Bacillus species. The present study investigated the effects of Bacillus sp. CT-5, isolated from cement, on compressive strength and water-absorption tests. The results showed a 36% increase in compressive strength of cement mortar with the addition of bacterial cells. Treated cubes absorbed six times less water than control cubes as a result of microbial calcite deposition. The current work demonstrated that production of "microbial concrete" by Bacillus sp. on constructed facilities could enhance the durability of building materials.